Is It Blocked or Dredged? Analysis of the Inhibitory Effect of Patent Assets and R&D Stock on the Market Value Impact of Patent Thickets in Chinese High-Tech Enterprises - Kai Luo; Jia Ren; Yibo Wang; Jun Wan (SAGE Open)
With the growing complexity of innovation, numerous patentees with patents needed for corporate innovation can act as a forest of thorns for companies, often referred to as “Patent Thickets.” These thickets increase the patenting transaction costs and depreciate the company’s market value. However, few studies have examined the mechanism of patent thickets’s impact on firms’ market value in the Chinese context. Based on the patent and market value data of 419 high-tech enterprises in China, this study finds that patent thickets reduce the market value of a company. However, firms with more patent assets can better protect themselves from the depreciation caused by patent thickets by building up their R&D resources, enabling them to generate more of their patented assets internally. This reduces the costs of purchasing patents from outside sources and can enhance the firm’s market value. This study suggests that to mitigate the negative impact of the patent thickets on firms’ market value, firms must build up their R&D inventories. By doing so, they can acquire more patents in-house, thereby protecting their patent rights.